The Efficiency of Using Chatgpt and Classpoint Online Apps in Improving English Teachers’ Formative Assessment Competence - Aswar; Abdul Haris Sunubi; Magdahalena Tjalla; Zulfah Fakhruddin; Ambo Dalle (Universitas Muhammadiyah Palu, 2025)
The high administrative workload often hinders teachers from developing innovative and interactive formative assessments. This study aims to examine the efficiency of using ChatGPT and ClassPoint in improving the formative assessment competencies of English teachers at junior high schools and to analyze teachers' perceptions of these technologies. This research employs a quantitative approach with a pre-experimental one-group pretest-post-test design, involving 9 English teachers from 7 schools. Data were collected through pretests and post-tests to measure teachers' formative assessment competencies and questionnaires to assess their perceptions. Statistical analysis utilized a paired t-test to compare pretest and post-test results, while descriptive statistics analysed perception data. The study results showed a significant improvement in teachers' formative assessment competencies, with scores increasing from 14.89 (pretest) to 31.11 (post-test), supported by a t-statistic value of -17.65 and a p-value < 0.01. The questionnaire analysis revealed highly positive responses, with over 90% of teachers strongly agreeing on the benefits of these technologies in creating diverse questions, speeding up the assessment process, and facilitating interactive formative assessments. These findings indicate that integrating ChatGPT and ClassPoint effectively enhances teachers' formative assessment competencies.